The comparison of sexual function based on female sexual function index between primiparous after vaginal delivery and post cesarean section - Hady Pratama, Bambang; Irianta, Trika; Syahrir, Syahruni; St., Nur Asni; Lotisna, David; Bangsawan, Nurbani (International Journal of Psychosocial Rehabilitation, 2020)
Sexual health after delivery is considered to be new and interesting. The purpose of the research was to find out mode about female sexual function index between primiparous after vaginal delivery and post-cesarean section. The research was using a cross-sectional analytical design. The samples were taken by using consecutive sampling from January-June 2019. There were 86 samples that are characterized as inclusion, which consist of 43 vaginal deliveries and 43 cesarean sections. After that, the sexual function was scored by filing in the FSFI (female sexual function index) questionnaires. The total score of the questionnaire was analyzed by having an independent test, the Chi square test to differ the subjective function, with a level of trust p ≤ 0.05. The character of the subject from the two groups appeared to be similar, for the result of the research could be ignored. The average period to have sexual intercourse for both groups is on the third month after the delivery. There were some statistically meaningful differences between the groups on the domains of desire, orgasm, satisfaction, and pain. On both sexual functions, it was found 18.6% on vaginal delivery and 2.3% on cesarean section. Therefore, it can be considered that there has been a significant difference in the sexual function between after vaginal delivery and post-cesarean section.